Prevalence and diversity of antibiotic resistance heterotrophic bacteria found along the Bintulu Rivers, Sarawak - Leong, Sui Sien; Hamli, Hadi; Abdul Rahim, Erra Fazira; Mustafa, Suhaili (UNIMAS Publisher, 2023)
The study aims (1) to isolate and characterise the heterotrophic bacteria from different rivers in Bintulu, Sarawak, (2) to investigate the hygienic condition of the rivers through faecal coliforms and (3) to determine the antibiotic resistance among the heterotrophic bacteria isolates. A total of 100 heterotrophic bacteria strains were identified from rivers of Bintulu, Sarawak. The characterisation of bacteria was performed using (GTG)5 fingerprinting to investigate their genetic distribution diversity and 16S rRNA gene sequencing. Microbiological variables tested including total viable count, coliform count, Escherichia coli confirmation test. Antibiotic susceptibility test was performed against 10 antibiotics. Sample collected from Sungai Teknik showed higher mean bacterial population size (log 4.48 ± 0.00 CFU/mL). Sungai Sibiu, Waterfront and Sungai Plan revealed the highest most probable number (MPN) index (>1,600 per mL). Each dendrogram showed 3 to 7 clusters of bacteria groups confirmed as Enterobacter spp. (40%), Acinetobacter spp. (13%), Bacillus spp. (13%), Klebsiella spp. (13%), Staphylococcus spp. (7%), Chromobacterium spp. (7%) and Citrobacter spp. (7%). All the heterotrophic bacteria isolated showed high resistance against ciprofloxacin (63.70 ± 33.40%), piperacillin (58.10 ± 31.37%), aztreonam (48.40 ± 30.95%) and more susceptible to tetracycline (3.30 ± 10.44%). Our findings highlight the multiple antibiotics resistance and microbiological analysis of heterotrophic bacteria found in polluted river water. The preservation of the river water is vital as hydrologic purposes, sustain the microbial composition, ecological integrity of the river.